From family to relational SCORE‐15: an alternative adult version of a systemic self‐report measure for couples and LGB People. Issue 1 (26th November 2015) - Teh, Yang Yang; Lask, Judith; Stratton, Peter
Abstract : SCORE‐15 is a self‐report measure developed for systemic approaches to therapy. This article describes a pilot study designed to test the reliability and content validity of the original SCORE‐15 for lesbian, gay and bisexual (LGB) adults in the UK. Quantitative data analyses conducted with an LGB sample ( n = 59) and a non‐LGB sample ( n = 57) found sufficient temporal and internal reliability in the SCORE‐15 but with some exceptions for the communication subscale. The content validity of SCORE‐15 was checked via group discussions with two clinical professionals groups ( n = 7) and a gay/bisexual men group ( n = 8). An alternative adult version of SCORE‐15 named the relational SCORE‐15 or the R‐SCORE‐15 was constructed and its content validity was checked by the original clinical professionals and an additional professional group ( n = 8). The R‐SCORE‐15 has content validity for clinical use with couples and LGB people in relationship therapy. Practitioner points: SCORE‐15 is a systemic self‐report measure reliable for routine clinical use with LGB people and couples in the UK to measure relational changes. The use of the term family affects the content validity of SCORE‐15 for LGB people and couples who may not regard family as their primary relationships. R‐SCORE‐15 is a recommended alternative to SCORE‐15 for couples, LGB people and those who may not define significant relationships via biology or marital ties.